Application of Rapid Impacts Assessment Matrix (RIAM) in Detecting Environmental Impacts of Chabahar Desalination Plant - Hasan Sayyad; Mohsen Shahriari Moghaddam; Malihe Erfani; Saeed Mohammadi (محیط زیست و توسعه فرابخشی)
Introduction: With the shortage of freshwater resources, the use of other available sources such as seas and oceans has increased, and new technologies in the field of desalination and treatment of saline waters have gained attention. The territorial waters of the Oman Sea and the Persian Gulf have created strong potential for the establishment of desalination plants for various uses in Iran. The sustainable development of desalination units requires adherence to environmental standards to prevent the increase of pollutants in the effluent. The Rapid Impact Assessment Matrix (RIAM) Method is a way to organize, analyze, and present the results of a comprehensive environmental assessment. The present study aimed to identify the positive and negative effects resulting from the operation of the Chabahar desalination plant during the operational phase on four environmental components (biological-ecological, physical-chemical, economic-operational, and social-cultural).Materials and Methods: After identifying the various phases of the project through library studies and gathering information from different sources, the components and elements of the environment in the affected area were examined and identified, categorized into four physical-chemical, biological-ecological, social-cultural, and economic-operational environments. Then, the effects of the Chabahar desalination plant's activities were assessed using RIAM during the operational phase. To this end, after identifying the various phases of this industrial unit, four components were identified and examined. The use of these four categories can serve as a suitable tool for environmental impact assessment studies, as it seems that each category can have subcategories for identifying environmental components, allowing for a more detailed and better analysis of the project's effects on different sectors. After the environmental components affected by the available options have been scored, the final score obtained indicates the environmental status of the project's activities.Results: The results showed that the most destructive consequences, with a score of -108, were related to the physical-chemical environment, while the most positive effects, with a score of +84, were in the social-cultural environment. In the physical-chemical environment section, this project has significant negative impacts on the region's environment. Given the project's proximity to the Sea of Oman and coral islands that host unique species and valuable ecosystem services, it is necessary to evaluate strategies to eliminate the negative effects resulting from changes in water quality and to minimize them. In the biological-ecological section, the most significant negative effects are on the fauna. The Chabahar desalination plant, in its operational phase, has 11 positive effects and 9 negative effects. Considering that this complex is a significant source of drinking water for the region and has meaningful positive impacts in the economic and social sectors, the continuation of its activities is permissible as long as environmental protection measures are observed.   Discussion: It is necessary to reduce the intensity of their effects by implementing corrective actions and monitoring environmental parameters at the wastewater disposal site, as well as continuously measuring the output pollutants in the surrounding environment and comparing them with national and international standards. The positive effects, due to being categorized as having very little change or positive effect, little change or positive effect, and change or positive effect, indicate the preference for carrying out the project over not doing it.